The molecular landscape of head and neck squamous cell carcinoma (HNSCC) - Chaturvedi V.K.; Hangloo A.; Pathak R.K.; Agarwal S.; Kushwaha A.; Gupta K.K.; Maurya S.; Singh A.K.; Verma V.; Singh M.P. (My University, 2025)
Head and neck squamous cell carcinoma (HNSCC) are a diverse group of malignancies which occur in the oral cavity, larynx, oropharynx and hypo pharynx. Head and neck cancer arises from a series of molecular alterations in a progression of skin carcinoma. Different risk factors associated with head and neck cancer includes tobacco chewing, high alcohol consumption and human papillomavirus (HPV) viral infection. Over-expression and mutations in genes lead to tumorigenesis in HNSCC through signalling pathways, such as EGFR, MAPk/ Erk VEGF, HER2, BRAF and RET. Targeted therapies and predictive biomarkers are needed in order to improve the treatment of toxicity in HNSCC. Cancer stem cells (CSCs) are immortal cells, having the capability of self-renewable, differentiation and tumorigenicity to make a constitutively own type of cancer cells. CSCs are identified by the bio markers, which are present on the cell surface such asCD44, CD24 and CD133. © 2017 by Nova Science Publishers, Inc. All rights reserved.